Livelihood Precarity of Migrants: Perspectives of African Refugees in Durban, South Africa - Umbyeyi, Beatrice Samson (Dhaulagiri Journal of Sociology and Anthropology, 2024)
Migrants and refugees face numerous socioeconomic and institutional challenges in the host cities and countries. They are excluded from full participation in the labor market, which makes them vulnerable to poverty. To survive, migrants and refugees join the informal economic sector. Informed by the Sustainable Livelihoods Framework (SLF), the article examines how African refugees in Durban make and maintain their livelihoods, including their encounters with marginalization. Participants were drawn from Congolese, Rwandese, and Burundian community groups living in the inner city of Durban. The snowballing sampling method was key in identifying the participants, while face-to-face interviews were used for data collection. The findings show that African refugees in Durban pursue diverse forms of livelihood in the informal sector. They are faced with numerous challenges, such as a lack of start-up capital, weak social networks to protect themselves and their businesses, bureaucratic challenges, discrimination, and xenophobic attacks. Regardless of these challenges, migrants still forge ahead by starting their businesses and making a living under the circumstances of precarity and marginalization.